Island Studies Journal, 14(1), Book Reviews - Island Studies Journal (Island Studies Journal, 2019)
Solution protocols to festering island disputes: ‘win-win’ solutions for the Diaoyu/Senkaku islands by Godfrey Baldacchino & contributors (reviewer: Romain Chuffart) Pacific futures, past and present by Warwick Anderson, Miranda Johnson, & Barbara Brookes (Eds.) (reviewer: Susanne Ferwerda) Archaeology of Pacific Oceania: inhabiting a sea of islands by Mike T. Carson (reviewer: David Burley) Relational undercurrents: contemporary art of the Caribbean archipelago by Tatiana Flores & Michelle A. Stephens (Eds.) (reviewer: Carlos Garrido Castellano)